A new species of Psydrax (Rubiaceae: Vanguerieae) from Tamil Nadu, India - Lincy, Joseph; Soosairaj, Sebastin; Dhivya, Rajappa; Arulanandam, John Peter (Phytotaxa, 2022)
Psydrax cudalorensis sp.nov. is described and illustrated from Tamil Nadu, India based on morphological and molecular evidence. Although morphologically P. cudalorensis appears to be similar to P. dicoccos, it is different from P. dicoccos in various aspects such as presence of pubescent stem, leaf, peduncle, pedicel, calyx, corolla, fruit and apiculate anther. ITS, rbcL and matK based phylogenetic analysis and SEM study of leaf surface also help to distinguish both the species.